Associations between clinical pathway concordance, cost, and survival outcomes for stage II colon cancer: a population-based study. (24th March 2023) - Milroy, Shannon; Wong, Judith; Eberg, Maria; Ieraci, Luciano; Forster, Katharina; Holloway, Claire M B; Sutherland, Jason M
Abstract: This study measures patient's concordance between clinical reference pathways with survival or cost among a population-based cohort of colon cancer patients applying a continuous measure of concordance. The primary hypothesis is that a higher concordance score with the clinical pathway is significantly associated with longer survival or lower cost. The study informs whether patient's adherence to a defined clinical pathway is beneficial to patients' outcomes or health system. An externally determined clinical pathway for colon cancer was used to identify treatment nodes in colon cancer care. Using observational data up to 2019, the study generated a continuous measure of pathway concordance. The study measured whether incremental improvements in pathway concordance were associated with survival and treatment costs. Concordance between patients' reference pathways and their observed trajectories of care was highly statistically associated with survivorship [hazard ratio: 0.95 (95% confidence interval, CI, 0.95–0.96)], showing that adherence to the clinical pathway was associated with a lower mortality rate. An increase in concordance was statistically significantly associated with a decrease in health system cost. When patients' care followed the clinical pathway, survival outcomes were better and total health system costs were lower in this cohort. This finding creates a compelling case for further research into understanding the barriers to pathway concordance and developing interventions to improve outcomes and help providers implement best practice care where appropriate.